The Influence of Ad Exposure and Social Influence on Purchase Decisions of Fore Coffee with Purchase Intention as an Intervening Variable - Via Nur Maria; Nurhayati Nurhayati; Andika Baskara; Sharina Osman; Joko Setyo Hartono (Value Added : Majalah Ekonomi dan Bisnis, 2026)
This study aims to examine the influence of ad exposure and social influence on the purchase decisions of Fore Coffee consumers in Semarang, with purchase intention serving as a mediating variable. The research addresses how ad exposure and social influence, both directly and indirectly, affect consumer purchase decisions based on the Stimulus-Organism-Response (S-O-R) theory. A quantitative research design was employed using a structured questionnaire distributed to 100 consumers of Fore Coffee Gayamsari Semarang selected through accidental sampling. The data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1.1.6 to test the relationships among the studied variables. The results indicate that ad exposure and social influence have a positive and significant effect on purchase intention. Purchase intention also positively and significantly affects purchase decisions. However, ad exposure and social influence do not have a direct significant effect on purchase decision. Furthermore, purchase intention mediates the relationship between ad exposure, social influence, and purchase decisions. The findings highlight the crucial role of purchase intention in shaping consumer purchase decisions and emphasize the importance of effective ad exposure and social influence in enhancing consumer purchase intention. Keywords: Ad exposure, Social Influence, Purchase Intention, Purchase Decisions, S-O-R Theory